1999
DOI: 10.1002/(sici)1097-4628(19991010)74:2<428::aid-app26>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Development of new ionomer blend membranes, their characterization, and their application in the perstractive separation of alkenes from alkene–alkane mixtures. I. Polymer modification, ionomer blend membrane preparation, and characterization

Abstract: In this contribution, the synthesis and characterization of novel ion-exchange blend membranes which contain the SO 3 Ag group for the application in the perstractive separation of alkene-alkane mixtures, where the Ag ϩ ion serves as facilitated transport site for the alkene via formation of a pi complex with the alkene double bond, is presented. In this part of the article, the synthesis and characterization of following blend membrane types are described: (1) acid-base blend membranes of ortho-sulfone-sulfon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The transport properties of the two materials are typical for these classes of membrane materials, based on perfluorinated and hydrocarbon polymers. This is clear from a compilation of D σ , D H 2 O , and D H 2 O P data for a variety of membrane materials, including Dow membranes of different equivalent weights, 226,255,260 Nafion/SiO 2 composites 243,244,[304][305][306] (including unpublished data from the laboratory of one of the authors), cross-linked polyarylenes, [307][308][309][310][311][312][313][314][315] and sulfonated poly-(phenoxyphosphazenes) 301 (Figure 19). The data points all center around the curves for Nafion and S-PEK, indicating essentially universal transport behavior for the two classes of membrane materials (only for S-POP are the transport coefficients somewhat lower, suggesting a more reduced percolation in this particular material).…”
Section: Hydrated Acidic Polymersmentioning
confidence: 99%
“…The transport properties of the two materials are typical for these classes of membrane materials, based on perfluorinated and hydrocarbon polymers. This is clear from a compilation of D σ , D H 2 O , and D H 2 O P data for a variety of membrane materials, including Dow membranes of different equivalent weights, 226,255,260 Nafion/SiO 2 composites 243,244,[304][305][306] (including unpublished data from the laboratory of one of the authors), cross-linked polyarylenes, [307][308][309][310][311][312][313][314][315] and sulfonated poly-(phenoxyphosphazenes) 301 (Figure 19). The data points all center around the curves for Nafion and S-PEK, indicating essentially universal transport behavior for the two classes of membrane materials (only for S-POP are the transport coefficients somewhat lower, suggesting a more reduced percolation in this particular material).…”
Section: Hydrated Acidic Polymersmentioning
confidence: 99%
“…The double peaks near 1080 cm −1 were caused by the asymmetric stretching vibration of the SiOSi in γ‐MPS and asymmetric stretching vibration of the SO in PSU. [ 36–38 ] Although the two peaks were overlapped, the dehydration condensation of the silanol group could still be seen from the change of the relative peak height. Except for these characteristic peaks, there is little difference in the three curves, and each of the infrared peaks in untreated PSU can be observed in the cross‐linked PSU/γ‐MPS, indicating that the cross‐linking reaction had no influence on the chemical structures of PSU, which confirmed that the intrinsic structures of PSU were not damaged during the cross‐linking process.…”
Section: Resultsmentioning
confidence: 99%
“…Guiver and coworkers5–11 did a lot of work on the lithiation of PSUs documented by several publications and patents. It was also shown by Kerres et al that sulfonic acid groups can be introduced into the electron‐deficient part of PSUs by a lithiation reaction with SO 2 oxidation of the PSU sulfinate with H 2 O 2 , KMnO 4 , or NaOCl to PSU–sulfonate12 or by a lithiation reaction with SO 2 Cl 2 hydrolysis of the PSU–sulfochloride with H 2 O, aqueous bases, or aqueous mineralic acids 13. Guiver and coworkers14, 15 reported the amination of PSU via the metalation route: first, lithiated PSU is reacted with tosylazide, and then the PSU–azide is reduced with NaBH 4 to PSU–NH 2 14, 15.…”
Section: Introductionmentioning
confidence: 94%